Proximal femoral bone geometry in osteoporotic hip fractures in Thailand - Vaseenon T. (Medical Association of Thailand, 2015)
© 2015, Medical Association of Thailand. All rights reserved. Background: A number of different bone geometries have been reported to be correlated with osteoporosis, bone mineral density and fractures. Those correlations are used for diagnosis, treatment and prediction of fracture risk in osteoporosis cases. However, there have been no studies of significant bone parameters predicting osteoporosis and hip fracture in Thailand. Objective: To evaluate the correlation between geometric parameters of the proximal femur and both the Singh index and bone mineral density as well as to investigate the relationship between those two metrics and osteoporotic hip fracture in the Thai population. Material and Method: Forty-four Thai patients with osteoporotic hip fractures and forty-five healthy Thai people matched for age and gender were included in the present study. Bone mineral density and bone geometry from plain hip radiographs of non-fracture sites in the fracture group and proximal femur radiographs of the same site in the healthy group were measured. That data were analyzed to determine levels of correlation. Bone geometries were also analyzed to determine hip fracture predictive capacity. Results: Correlation between the Singh index and bone mineral density was significant (p<0.01), with a moderate degree of agreement. The radiograph measurement of the width of the femoral medial neck cortex was the only parameter which was statistically significantly correlated with both osteoporosis and with osteoporotic hip fracture (p = 0.014 and p = 0.035, respectively). Each 1 mm reduction in the width of the femoral medial neck cortex increased the osteoporotic hip fracture risk by a factor of 2.7 (OR = 0.37, 95% CI = 0.15-0.93). Conclusion: In the Thai population, bone geometry from plain radiographs can help predict the risk of osteoporotic hip fracture. Osteoporosis is correlated with a low Singh index value. The width of the femoral medial neck cortex is a reliable predictor of hip fracture risk.